The AirAsia Search: Positive Precedent for Future Cooperation - Tsjeng, Henrick Zhizhao (2015)
The search for AirAsia Flight 8501 has been largely commended as a success. While not without obstacles, the multilateral efforts led by host country Indonesia contributed to a smooth search. This success can be a positive precedent for future cooperation.